Harm of the Transcendency of Education Stage and the Preventive Strategies - Li, Wenwen (Transactions on Social Science, Education and Humanities Research, 2023)
The primary school tendency of kindergarten education not only harms the development of children’s physical and mental health, but also affects the development of children’s education as a whole in China. Although China has begun to deal with the problem of “primary schooling” in kindergarten education, the national and local education authorities have also issued a series of policies and regulations that resolutely prevent the “primary school” of kindergarten education. The problem of “primary school” tends to be alleviated. But so far, the primary school tendency of kindergarten education still exists. Based on this, this paper studies the harm of kindergarten education primary school including the harm to young children themselves and Harm to the development of early childhood education. At the same time, the author puts forward the preventive strategies from the aspect of government, the quality of preschool teachers and education system, hoping to help the development of kindergarten education.